2018
DOI: 10.1002/bem.22134
|View full text |Cite
|
Sign up to set email alerts
|

The interphase interval within a bipolar nanosecond electric pulse modulates bipolar cancellation

Abstract: Nanosecond electric pulse (nsEP) exposure generates an array of physiological effects. The extent of these effects is impacted by whether the nsEP is a unipolar (UP) or bipolar (BP) exposure. A 600 ns pulse can generate 71% more YO-PRO-1 uptake compared to a 600 ns + 600 ns pulse exposure. This observation is termed "bipolar cancellation" (BPC) because despite the BP nsEP consisting of an additional 600 ns pulse, it generates reduced membrane perturbation. BPC is achieved by varying pulse amplitudes, and symme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Similarly, it was reported that a negative pulse three times the duration of the first caused complete loss of bipolar cancellation [10]. Moreover, the study revealed that cancellation is progressively reduced by increasing the interphase interval within the pulse [1], [4], and it can be completely reversed with a delay larger than 10 ms [8]. In addition, the delivery of two identical pulses of the same polarity (paired pulses) separated by a certain time gap was investigated.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…Similarly, it was reported that a negative pulse three times the duration of the first caused complete loss of bipolar cancellation [10]. Moreover, the study revealed that cancellation is progressively reduced by increasing the interphase interval within the pulse [1], [4], and it can be completely reversed with a delay larger than 10 ms [8]. In addition, the delivery of two identical pulses of the same polarity (paired pulses) separated by a certain time gap was investigated.…”
Section: Introductionmentioning
confidence: 80%
“…The electrodes, modeled as perfect electric conductors, are connected through a Tee adaptor to the generator and to a 50 Ω high-voltage resistor placed in parallel to ensure impedance matching with the generator. The impedance of the electrodes delivery systems is higher than one hundred Ω [1], [8], [10], [40], [42], [43]. Thus, although the applied power is mainly dissipated in the 50 Ω resistor, the electric field applied between the electrodes is more prevalent in terms of cell perturbation.…”
Section: High-voltage Delayed Nanosecond Pulsesmentioning
confidence: 99%
See 3 more Smart Citations